Multiculturalism Integrity in Contemporary Music - Kholid, Dody Mohamad (SOSIOHUMANIKA, 2015)
ABSTRACT: Art is one of the elements of the culture. It is the result of thought, taste, needs, and human behavior. In addition to the result of human action, the existence and development of culture is also affected by natural factors, where the culture is alive, growing, and interacting among living things in its environment. A culture is highly dependent and influenced by living things (especially humans) and natural surroundings. Therefore, when there is interaction between human beings and nature and the environment, it will create a culture. And music, as a form of culture, is one of the examples that develop based on human interaction. Development of music from the past until now go through various changes, like that occur in contemporary music. Changes in contemporary music are always in accordance with the changing of times when the music evolved. Thus, the shape of contemporary musical composition always changes in terms of instruments, structures, techniques, and forms. While, the multiculturalism integrity is a process or an event when several different cultures are gathered and incorporated in a container that interacts to produce a new product. That is to say, the process of multiculturalism is a cultural development generated by the influence of various foreign cultures. The cultural mixing can occur in any case, one of which is on contemporary music as the form of musical development, that is ever-changing developments in accordance with the changing times.KEY WORD: Culture, music, composition, contemporary music, multiculturalism, different cultures, changing times, and integrity.Â RESUME: âIntegritas Multikulturalisme dalam Musik Kontemporerâ. Seni adalah salah satu unsur budaya. Ia adalah hasil dari pemikiran, rasa, kebutuhan, dan perilaku manusia. Selain hasil tindakan manusia, keberadaan dan pengembangan budaya juga dipengaruhi oleh faktor alam, dimana budaya hidup, tumbuh, dan berinteraksi diantara yang tinggal di lingkungannya. Sebuah budaya sangat tergantung dan dipengaruhi oleh makhluk hidup (khususnya manusia) dan alam sekitarnya. Karenanya, ketika ada interaksi antara manusia dengan alam dan lingkungan, itu akan menciptakan budaya. Dan musik, sebagai bentuk budaya, adalah salah satu contoh yang berkembang berdasarkan interaksi manusia. Perkembangan musik dari masa lalu sampai sekarang melalui berbagai perubahan, seperti yang terjadi dalam musik kontemporer. Perubahan musik kontemporer selalu sesuai dengan perubahan zaman ketika musik berevolusi. Dengan demikian, bentuk komposisi musik kontemporer selalu berubah dalam hal instrumen, struktur, teknik, dan bentuk. Sementara itu, integritas multikulturalisme adalah sebuah proses atau suatu kejadian pertemuan beberapa budaya yang berbeda, dan tergabung dalam suatu wadah yang berinteraksi untuk menghasilkan suatu produk yang baru. Artinya, proses multikultur adalah sebuah perkembangan budaya yang dihasilkan oleh pengaruh dari berbagai macam budaya luar. Pencampuran budaya tersebut bisa terjadi dalam hal apapun, salah satunya adalah pada musik kontemporer yang merupakan wujud perkembangan musik, yang selalu berubah sesuai dengan perkembangan zaman.KATA KUNCI: Budaya, musik, komposisi, musik kontemporer, multikulturalisme, perbedaan budaya, perkambangan zaman, dan integritas.About the Author: Dody Mohamad Kholid is a Lecturer at the Department of Music Education FPSD UPI (Faculty of Art and Design Education, Indonesia University of Education), Jalan Dr. Setiabudi No.229 Bandung 40154, West Java, Indonesia. E-mail: dodykholid@gmail.comHow to cite this article? Kholid, Dody Mohamad. (2015). âMulticulturalism Integrity in Contemporary Musicâ in SOSIOHUMANIKA: Jurnal Pendidikan Sains Sosial dan Kemanusiaan, Vol.8(1) Mei, pp.67-76. Bandung, Indonesia: Minda Masagi Press, UNHAS Makassar, and UNIPA Surabaya, ISSN 1979-0112. Chronicle of the article: Accepted (December 22, 2014); Revised (March 2, 2015); and Published (May 30, 2015).